2020
DOI: 10.1111/jfbc.13136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre‐storage ascorbic acid andAloe veragel coating application on enzymatic browning and quality of lotus root slices

Abstract: The effect of ascorbic acid [AA (1%)] and Aloe vera gel [AVG (50%)] coating alone and in combination was investigated on enzymatic browning and quality of lotus root slices during storage at 20 ± 1°C. The combined application of AA and AVG coating delayed surface browning, reduced increase in relative electrolyte leakage (REL) and showed higher overall visual quality (OVQ). Similarly, AA and AVG combined treatment reduced superoxide anion (O2-·) and hydrogen peroxide (H2O2) production and malondialdehyde (MDA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 54 publications
(123 reference statements)
2
20
0
Order By: Relevance
“…The minimum values of REL and MDA content of AVBO1 and AVBO2 samples could be related to the higher efficacy of treatments to protect cell membrane structure. In this regard, the results of REL and MDA are in a line with studies ofAli et al (2019c) on lotus root by application of ascorbic acid and A. vera gel andHuang et al (2019) on mushroom by chitosan and guar gum coating. In current research we found considerable correlation (0.860 ** ), between REL and MDA.…”
supporting
confidence: 85%
“…The minimum values of REL and MDA content of AVBO1 and AVBO2 samples could be related to the higher efficacy of treatments to protect cell membrane structure. In this regard, the results of REL and MDA are in a line with studies ofAli et al (2019c) on lotus root by application of ascorbic acid and A. vera gel andHuang et al (2019) on mushroom by chitosan and guar gum coating. In current research we found considerable correlation (0.860 ** ), between REL and MDA.…”
supporting
confidence: 85%
“…It has been found in the literature that exogenous application of ALV combined with natural edible coatings such as guar gum (Ebrahimi & Rastegar, 2020), basil seed mucilage (Nourozi & Sayyari, 2020), banana starch (Pinzon et al, 2020), gum arabic (Anjum et al, 2020), chitosan (Khatri et al, 2020;Vieira et al, 2016), Fagonia indica plant extract ), rosehip oil (Martínez-Romero et al, 2017, shellac (Chauhan et al, 2015), xanthan gum (Abraham & Banerjee, 2018), tragacanth gum (Mohebbi et al, 2012), wheat grass juice (Ratra et al, 2016), neem extract (Jaiswal et al, 2017), and garlic oil upregulated its expression on end quality. Likewise, synthetic coatings including ascorbic acid (Ali, Anjum, Nawaz, Naz, et al, 2019;Sogvar et al, 2016), cystine (Song et al, 2013), salicylic acid (Peyro et al, 2017;Rasouli et al, 2019), hydroxypropyl methylcellulose (Farina, Passafiume, Tinebra, Scuderi, et al, 2020) gave promising results for maintaining the fruit quality (Table 1). Although, it must not be conceived that combination always goes better while ALV application can alone be proved as promising technique to improve the postharvest shelf and storage life with good eating quality.…”
Section: Aloe Ver a Appli C Ati On In Comb Inati On With Other P Osmentioning
confidence: 99%
“…During postharvest handling, susceptibility of fruits and vegetables to enzymatic browning is considered as most undesirable disorder which limits their marketability, consumer acceptance, and cause huge economic loss (Sivakumar & Korsten, 2010). Browning has been associated with several factors including water loss, mechanical injuries, infection (pathogenic), oxidative stress, lipid peroxidation, mixing of phenolic compound with peroxidase and polyphenol oxidase enzymes, and loss of cellular compartmentalization (Ali et al, 2019;Ali et al, 2019a;Jiang et al, 2004;Zhang et al, 2018). Most recently, anti-browning property of ALV coating has been reported during storage and shelf life studies.…”
Section: Enzymatic Browningmentioning
confidence: 99%
“…ROS accumulation generally accompanies the browning process after wounding ( Ali et al, 2020). Ali et al (2020) reported that decreases in H 2 O 2 and O 2 ⋅contents were accompanied by less browning in lotus root slices treated with ascorbic acid and an aloe vera gel coating than in control slices.…”
Section: Contents Of Malondialdehyde H 2 O 2 and O 2 ⋅And Antioxidant Capacitymentioning
confidence: 99%